2002
DOI: 10.1007/s00415-002-0692-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac involvement and CTG expansion in myotonic dystrophy

Abstract: Although cardiac complications are well known in myotonic dystrophy (DM), patients rarely manifest symptoms of cardiac disease, and if so they most often show conduction abnormalities or arrhythmia. In this study, specific cardiac findings were reviewed in 79 patients with DM. No correlation was found between the cardiac assessments and the CTG expansion. Thus, for a single patient the cardiac involvement in the disease can not be predicted from the findings of the genetic investigation. On the other hand, a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 21 publications
1
25
0
2
Order By: Relevance
“…Improvement of the TTE in a single patient (CR) was attributed to β-blocker therapy. The absent correlation between the SAP and the CTG-repeat size is in line with previous findings [17,19,29,30]. Patient NE with a fractional shortening of 10% died 1 year after the 10-year follow-up.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Improvement of the TTE in a single patient (CR) was attributed to β-blocker therapy. The absent correlation between the SAP and the CTG-repeat size is in line with previous findings [17,19,29,30]. Patient NE with a fractional shortening of 10% died 1 year after the 10-year follow-up.…”
Section: Discussionsupporting
confidence: 89%
“…Concerning the correlation between the CTG-repeat size and CI there are conflicting results. Some authors showed a clear positive correlation between the CTG-repeat expansion and CI [22,27,28], whereas others could not confirm these results [17,18,29]. Factors in addition to the CTG-repeat size seem to determine severity and progression of CI in MD [30].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Although such a correlation between the extent of CTG repeats and the degree of cardiac involvement has been described in some series, others have shown conflicting results (9,17,18,25,(34)(35)(36)(37)(38)(39). Of note is the study by Lazarus et al (17); using precise invasive electrophysiological measurements, the study was unable to show such a relationship between conduction delays and the extent of CTG repeats.…”
Section: Discussionmentioning
confidence: 96%
“…Cardiac surveillance, including routine monitoring of electrocardiograms, may detect early DCM development in both DMD and BMD (109). In addition, in 32% of MD1 patients with a normal ECG, the 24 h Holter monitoring showed arrhythmias and conduction abnormalities (110). In MD1, Holter monitoring should be performed on a regular basis, at intervals not >6 months (111).…”
Section: Currently Used Techniques For the Evaluation Of Heart Involvmentioning
confidence: 99%